On finite dimensional realizations for the term structure of futures prices - Tomas Björk; Magnus Blix; Camilla Landén (Stockholm School of Economics, The Economic Research Institute (EFI), 2005)
We consider HJM type models for the term structure of futures prices, where the volatility is allowed to be an arbitrary smooth functional of the present futures privce curve. Using a Lie algebraic approach we investigate when the infinite dimensional futures price process can be realized by a finite dimensional Markovian state space model, and we give general necessary and sufficient conditions, in terms of the volatility structure, for the existence of a finite dimensional realization. We study a number of concrefe applications including a recently developed model for gas futures. In particular we provide necessary and sufficient conditions for when the induced spot price is a Markov process. In particular we can prove that the only HJM type futures price models with spot price dependent volatility structures which generically possess a spot price realization are the affine ones. These models are thus the only generic spot price models from a futures price term structure point of view.
Keywords: G13; 330; futures contract; term structure; Lie algebra; finite dimensional realisation; Termingeschäft; Volatilität; Markovscher Prozess; Zustandsraummodell